2016
DOI: 10.1007/s13347-016-0243-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital Art as ‘Monetised Graphics’: Enforcing Intellectual Property on the Blockchain

Abstract: In a global economic landscape of hyper-commodification and financialisation, efforts to assimilate digital art into the high-stakes commercial art market have so far been rather unsuccessful, presumably because digital artworks cannot easily assume the status of precious object worthy of collection. This essay explores the use of blockchain technologies in attempts to create proprietary digital art markets in which uncommodifiable digital artworks are financialised as artificially scarce commodities. Using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(53 citation statements)
references
References 28 publications
0
36
0
1
Order By: Relevance
“…It is necessary to point out that proving of existence is quite typical for similar platforms too. For example, as Martin Zeilinger says, Monegraph allows creators, owners, and collectors to document and verify the authenticity and provenance of the digital artefacts [8]. It should be also noted that the deposition of a certain copyright or related rights object (for example, a literary work) means that it was put into the decentralized ledger in a digital form.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to point out that proving of existence is quite typical for similar platforms too. For example, as Martin Zeilinger says, Monegraph allows creators, owners, and collectors to document and verify the authenticity and provenance of the digital artefacts [8]. It should be also noted that the deposition of a certain copyright or related rights object (for example, a literary work) means that it was put into the decentralized ledger in a digital form.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the use of Blockchain may disrupt the existing creative distribution networks, with [15] questioning how market will react to increased copyright control. Others question whether the "models of centralized finance will be far from being disrupted but rather reinforced" [26]. In a nutshell, literature points to some challenges inherent to the Blockchain technology, but also raises important issues related to implementation and market acceptance.…”
Section: % 25%mentioning
confidence: 99%
“…Intellectual property law has emerged as a way to prevent unauthorized distribution of creative expressions due to easy mechanical, technological, and digital reproduction [26]. Some papers have researched the articulation of Blockchain with traditional copyright law [17].…”
Section: % 25%mentioning
confidence: 99%
“…Therefore, Monegraph enters into the political economy of copyright and its troubled interaction with the digital. However, the set of copyright tools enabled by the system might be insufficient to actually protect artists, as Martin Zeilinger () has pointed out. What is more substantial, though, is that Monegraph has conceptually narrowed the possibilities of the digital, especially with respect to digital arts.…”
Section: Blockchains As Notational Technologies: the Example Of Monegmentioning
confidence: 99%